О некоторых внутривидовых формах триходины черной — Trichodina nigra Lom., I960 (Ciliata, Urceolariidae) - Костенко, С.М. (Вестник зоологии, 1969)
Parasitic infusoria of Urceolariidae family were the subject of the investigation. New forms of Trichodina nigra Lorn, 1960, are described and their morphological characteristics are given.